Peran Strategis SDM dalam Mendorong Kesuksesan PT Astra International Tbk - Rismawati, Rismawati; Elvianto, Damas; Fauziyah, Syahwatul Khalda (Lembaga Yasin AlSys, 2025)
The development of the disruption era and globalization demands that companies manage human resources (HR) more effectively and adaptively in order to maintain competitiveness and business sustainability. This study aims to describe and analyze the human resource management strategy implemented by PT Astra International Tbk in responding to these challenges. Using a descriptive qualitative approach, data were collected through semi-structured interviews, documentation, and literature review. The results show that Astra applies a Total Human Capital Management approach, which includes competency-based recruitment, continuous training, career development based on meritocracy, and a fair and transparent reward system. The use of digital technology is also an integral part of HR management, such as the implementation of e-learning, performance dashboards, and a hybrid work system. In addition, Astra reinforces an inclusive work culture and designs retention programs specifically tailored to the millennial and Gen Z generations, taking into account their unique characteristics and expectations. This integrated and adaptive HR strategy has proven effective in enhancing organizational competitiveness and long-term sustainability. These findings offer practical implications for other companies seeking to build an HR ecosystem that is responsive to change, value-based, and future-oriented.